Agreement/disagreement between caloric and video head impulse tests: does it reveal something? Report from three individuals with auditory neuropathy spectrum disorder. (2nd January 2019) - Sinha, Sujeet Kumar; Bansal, Shalini; Neupane, Anuj Kumar
Abstract: Introduction: Neuropathies of the eighth nerve may be due to primary demyelination or axonal diseases or by mixed disorder of the two resulting in normal cochlear functioning and affected afferent neural conduction in the auditory pathway. Since vestibular nerve is a part of the eighth nerve, there is a possibility of vestibular nerve also getting affected in individuals with auditory neuropathy. Aims and objectives: The aim of the study was to understand the correlation between caloric and video head impulse test (vHIT) results in individuals with auditory neuropathy. Method: A total of three participants diagnosed as having auditory neuropathy, with no other otological or neurological problems were taken for the study. Bithermal caloric test and vHIT were administered for all the participants. Results: In two of the participants with auditory neuropathy spectrum disorder (ANSD), hypofunctional caloric responses were observed along with reduced vestibuloocular reflex (VOR) gain and refixation saccades. However, third participant had hypofunctional caloric response along with normal VOR gain and absent refixation saccade. Discussions: In the present study, the caloric responses were found to be hypofunctional in all three participants suggesting vestibular deficits. Presence of hypofunctional caloric responses reduced VOR gain and refixation saccades suggested greater involvement of vestibular deficit. Conclusions: Findings of the study suggest that in addition to the auditory system, the vestibular system may also be affected in ANSD.